TINGKAT PENGETAHUAN, SIKAP, DAN KETERAMPILAN IBU DALAM PENANGANAN AWAL DIARE PADA BALITA - Aryani, Puspita Ayu; Margono, Margono; Hernayanti, Munica Rita (Jurnal Kesehatan Ibu dan Anak, 2015)
The WHO reported that themain cause of death in toddlers ( post neonatal ) is diarrhea.Death in toddlers due to diarrhea at 14%.The provision of a liquid a substitute ( a liquid rehidrasi ) as initial handling diarrhea can reduce the rate death from dehydration.The behavior of the people in penatalaksanaan diarrhea at households not yet good.The purpose of this study is to find the level of knowledge attitude, and skill mother in initial handling diarrhea in hamlet Papringan Sleman 2015.A method of this research are thoughts of diskriptif cross sectional.The subject of study is 54 mother who have babies in rw 02 and rw 05 hamlet papringan.A measuring instrument the research uses a questionnaire covered right wrong, likert, the manufacture of and checklist of sugar solutions salt.The result of this research aremostlymotherwas & it; 45 years educatedmiddle exposed to information and the source of exposure to the majority of information from a source of direct. The knowledge of the most of it.The attitude towards the initial diarrhea in toddlers and 50 %to 50 %, there is no support mostly mother has enough in research skills but there are two items less